Analysis of the Effect of Government Spending and PDRB on Human Development Index in Districts/Cities of Bengkulu Province - Annisa, Dinda Sinsilia; Indraswanti, Bertha Iin Esti (PT FORMOSA CENDEKIA GLOBAL, 2024)
HDI, or Human Development Index, is a measure used to assess the level of human quality development in a country. The purpose of this research is to see the effect of government expenditure on education and health as well as GRDP on the level of HDI in the Regency/City of Bengkulu Province. The analysis method in this study uses panel data regression and uses Stata/MP 14.0 software. Panel data covering 10 regencies/cities in Bengkulu Province for a period of 7 years, namely 2015-2021. The results of the research conducted have a significant influence between health expenditure, and GRDP on HDI in the Regency/City of Bengkulu Province. However, education expenditure does not have a significant effect on HDI in the Regency/City of Bengkulu Province. Through health expenditure and GRDP, it is hoped that it can improve the quality of life of people in Bengkulu Province.